2008
DOI: 10.1001/archpedi.162.7.634
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Violence Among Female and Male College Undergraduate Students

Abstract: Relationship violence is prevalent among college students and frequently occurs before college. Emotional violence was most frequent before college; sexual and emotional violence were equally common during college. Women reported more victimization than men, but male victimization was common. Men perpetrated more sexual violence; women perpetrated more physical violence. Physical violence and emotional violence were most often committed by partners, while sexual violence was less likely to be partner related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 57 publications
9
66
2
Order By: Relevance
“…Past year rates of IPA in heterosexual relationships range from 12% to 30% (Caetano, Cunradi, Schafer, & Clark, 2000;Cunradi, Todd, Duke, & Ames, 2009;Smith, Thornton, DeVelis, Earp, & Coker, 2002). IPA among college dating couples is even more prevalent, with approximately 20% to 50% of this age group reporting aggression (Cogan & Fennell, 2007;Forke, Myers, Cantallozzi, & Schwarz, 2008;Straus, 2004). The consequences of IPA in college samples are varied and include physical health complaints (Amar & Gennaro, 2005) and psychological difficulties such as depression, anxiety, and somatization symptoms (Clements, Ogle, & Sabourin, 2005;Kaura & Lohman, 2007).…”
mentioning
confidence: 99%
“…Past year rates of IPA in heterosexual relationships range from 12% to 30% (Caetano, Cunradi, Schafer, & Clark, 2000;Cunradi, Todd, Duke, & Ames, 2009;Smith, Thornton, DeVelis, Earp, & Coker, 2002). IPA among college dating couples is even more prevalent, with approximately 20% to 50% of this age group reporting aggression (Cogan & Fennell, 2007;Forke, Myers, Cantallozzi, & Schwarz, 2008;Straus, 2004). The consequences of IPA in college samples are varied and include physical health complaints (Amar & Gennaro, 2005) and psychological difficulties such as depression, anxiety, and somatization symptoms (Clements, Ogle, & Sabourin, 2005;Kaura & Lohman, 2007).…”
mentioning
confidence: 99%
“…Previous studies typically explored college women's experiences with victimization, although a growing literature has examined the victimization experiences of college men (Avant et al, 2010;Forke et al, 2008;Hines & Saudino, 2003). Consistent with previous research (Forke et al, 2008;Hines & Saudino, 2003), prevalence of physical abuse by a partner is similar for men and women. Thus, in terms of overall prevalence intimate partner physical victimization appears to be fairly gender symmetrical.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have found that status or power inequalities, patriarchal and traditional beliefs about gender roles play a role in the perpetration of IPV (Anderson, 1997;Atkinson et al, 2005;Claes & Rosenthal, 1990;DeKeseredy & Schwartz, 1998;Gelles, 1974;Macmillan & Gartner, 1999;McCloskey, 1996;Yodanis, 2004). Two macro-level studies by Yllo (1983Yllo ( , 1984 In college samples, both men and women have been found to experience abusive behaviors while in college (Harned, 2001;Forke et al, 2008;Perry & Fromuth, 2005). The concept of IPV perpetrated by women is contrary to feminist theory, in that it runs counter to arguments of patriarchal power and control.…”
Section: Feminist Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…IPV is prominent among college students, with 85.4% of women and 55.0% of men reporting perpetration of sexual, emotional and/or physical violence against their partners in one particularly well-conducted study (Forke, Myers, Catallozzi, & Schwarz, 2008). However, people tend to overlook the fact that IPV can involve more than just physical violence.…”
Section: Studymentioning
confidence: 99%